Recent Advances of Deep Learning in Bioinformatics and Computational Biology - Tang, Binhua; Pan, Zixiang; Yin, Kang; Khateeb, Asif (Frontiers in Genetics, 2019)
Extracting inherent valuable knowledge from omics big data remains as a haunting problem in bioinformatics and computational biology. Deep learning, as an emerging branch from machine learning, has exhibited unprecedented performance in quite a few applications from academia and industry. We highlight the difference and similarity in widely utilized models in deep learning studies, through discussing their basic structures, and reviewing diverse applications and disadvantages. We anticipate the work can serve as a meaningful perspective for further development of its theory, algorithm and application in bioinformatic and computational biology.